Norway : Financial Sector Assessment Program-Technical Note-Banking Regulation and Supervision. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
This note presents a targeted review of selected aspects in the regulation and supervision of banks in Norway. The review is carried out as part of the 2020 Norway Financial Sector Assessment Program (FSAP) and the findings and recommendations are based on the regulatory framework in place and the supervisory practices employed at end-October 2019. The note focuses on the powers and responsibilities, independence, and resourcing of Finanstilsynet (FSA); its supervisory approach and enforcement powers and practices; key aspects of the prudential framework; and mechanisms to prevent abuse of financial services.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet